Біотопічний розподіл водних черевоногих молюсків витоків річки Луга - Горанська, Людмила; Теплюк, Вадим; Goranska, Lyudmila; Tepliuk, Vadym (Східноєвропейський національний університет імені Лесі Українки, 2016)
У роботі розглянуто особливості біотопічного розподілу водних черевоногих молюсків витоків річки Луга. Установлено, що малакофауна представлена 13 видами з двох підкласів: Prosobranchia – 2, Pulmonata – 11 видів. З’ясовано закономірності чисельності та поширення водних черевоногих у верхній течії річки Луга, ме-ліоративних каналах і ставках. The paper reviewed the biotopical distribution of aquatic gastropods of origins Luga River. It has been established that fauna of mollusks has 13 species from 2 subclasses and 5 families: Prosobranchia – 2 (Bithyniidae – 1, Viviparidae – 1), Pulmonata – 11 (Lymnaeidae – 5, Planorbidae – 5, Acroloxidae – 1) species. There is the greatest abundance of representatives of families Planorbidae (47,1 %) and Lymnaeidae (36,6 %). Lymnaea stagnalis (33,7 %) and Planorbis planorbis (21,5 %) are the mass species. Mostly mollusks inhabit in quiet shallow areas (0,2–0,5 m) of standing or slightly flowing (0,1–0,4 m/s) parts of reservoirs, which usually are overgrown with aquatic vegetation. Species composition of gastropods of the upper course of the river has 8 species, ponds – 8 species, meliorative channel – 6 species
Bio-ecological Analysis of Water Gastropods of Origins Luga River.
Keywords: черевоногі молюски; ставки; меліоративні канали; річка; поширення; чисельність; фауністичні комплекси; gastropods; meliorative channel; ponds; the river; the distribution; the abundance; species composition